Need for a policy of public space in the populated centers of the municipality of Chia (2016)
Chia, is a Municipality that, because of its proximity to Bogota and the opportunities it represents for many families, has been presenting unplanned and unstructured growth mainly in its population and in its constructive development, causing rural areas to lose their vocation And that, due to the eleven existing rural population centers, the absence of internal regulations, the consolidation of the area of urban expansion and the development of residential units of medium density in the eastern hills, mainly generate the need to propose a Public Space Policy Public that seeks to establish tools to reduce the quantitative and qualitative deficit of effective public space existing in the Municipality achieving by 2028 to reach fifteen square meters (15m2) per habitant.